Galangal-Cinnamon Spice Mixture Blocks the Coronavirus Infection Pathway through Inhibition of SARS-CoV-2 MPro, Three HCoV-229E Targets; Quantum-Chemical Calculations Support In Vitro Evaluation - Doaa G. El-Hosari; Wesam M. Hussein; Marwa O. Elgendy; Sara O. Elgendy; Ahmed R. N. Ibrahim; Alzhraa M. Fahmy; Afnan Hassan; Fatma Alzahraa Mokhtar; Modather F. Hussein; Mohamed E. A. Abdelrahim; Eman G. Haggag (MDPI AG, 2023)
Natural products such as domestic herbal drugs which are easily accessible and cost-effective can be used as a complementary treatment in mild and moderate COVID-19 cases. This study aimed to detect and describe the efficiency of phenolics detected in the galangal-cinnamon mixture in the inhibition of SARS-CoV-2's different protein targets. The potential antiviral effect of galangal-cinnamon aqueous extract (GCAE) against Low Pathogenic HCoV-229E was assessed using cytopathic effect inhibition assay and the crystal violet method. Low Pathogenic HCoV-229E was used as it is safer for in vitro laboratory experimentation and due to the conformation and the binding pockets similarity between HCoV-229E and SARS-CoV-2 MPro. The GCAE showed a significant antiviral effect against HCoV-229E (IC50 15.083 µg/mL). Twelve phenolic compounds were detected in the extract with ellagic, cinnamic, and gallic acids being the major identified phenolic acids, while rutin was the major identified flavonoid glycoside. Quantum-chemical calculations were made to find molecular properties using the DFT/B3LYP method with 6-311++G(2d,2p) basis set. Quantum-chemical values such as EHOMO, ELUMO, energy gap, ionization potential, chemical hardness, softness, and electronegativity values were calculated and discussed. Phenolic compounds detected by HPLC-DAD-UV in the GCAE were docked into the active site of 3 HCoV-229E targets (PDB IDs. 2ZU2, 6U7G, 7VN9, and 6WTT) to find the potential inhibitors that block the Coronavirus infection pathways from quantum and docking data for these compounds. There are good adaptations between the theoretical and experimental results showing that rutin has the highest activity against Low Pathogenic HCoV-229E in the GCAE extract.